A four-layer brazing aluminum composite material and a preparation method thereof

CN121339761BActive Publication Date: 2026-09-18CHANGSHA ZHONGXING ALUMINUM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511480501.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-16
Publication Date
2026-09-18
Estimated Expiration
2045-10-16

AI Technical Summary

Technical Problem

型材和钎焊是目前两种主流的液冷板,钎焊式的流道多变,温差均匀性更高,搅拌摩擦焊式强度更高,流道固定,温差较差

Benefits of technology

(1)本发明的复合材料中钎焊层含有特定比例的Si、Sr和Bi元素,这些元素的协同作用赋予了钎焊层良好的钎焊性能。Si元素能够降低铝合金的熔点,提高液态钎料的流动性,使得在钎焊过程中能够更好地填充焊缝间隙,确保焊接的牢固性。Sr元素具有细化晶粒的作用,有助于提高钎焊层的强度和韧性,增强其抗疲劳性能。Bi元素则可以改善钎料的润湿性,使钎料能够更好地与母材结合,提高焊接接头的质量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121339761B_ABST
    Figure CN121339761B_ABST
Patent Text Reader

Abstract

This application provides a four-layer brazed aluminum composite material and its preparation method, belonging to the technical field of aluminum-based materials. The composite material comprises, from bottom to top: a brazing layer: an aluminum alloy containing 9.3-9.8% Si, 0.02-0.04% Sr, and 0.05-0.1% Bi; a gradient barrier layer: an Al-Mn-Cu alloy with a gradient composition distribution, wherein the Si content near the core is 0.8-1.0%, the Si content near the brazing side is 0.3-0.5%, and it contains 0.01-0.02% Ce; a core material: an Al-Mg-Si alloy containing 0.8-1.2% Mg, 0.4-0.8% Si, 0.08-0.12% Zr, and 0.04-0.06% Cr; and an anti-corrosion layer: an Al-Mn alloy containing 0.8-1.0% Mn and 0.05-0.1% Ti. This invention exhibits excellent brazing performance, tensile strength, and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of aluminum-based materials technology, and in particular to a four-layer brazed aluminum composite material and its preparation method. Background Technology

[0002] With the rapid development of renewable energy and the adjustment of energy consumption structure, energy storage technology has become one of the key technologies for solving the intermittent power generation of renewable energy and grid fluctuations. Maintaining the battery cells within a suitable temperature range is extremely important for energy storage systems. Since cell temperature has a significant impact on the number of charge-discharge cycles, and 25-30℃ is the optimal temperature for cell charging and discharging, the choice of thermal management scheme is a crucial factor affecting battery performance. Currently, the most mature and widely used solution is liquid plate cooling, which uses a liquid cooling plate in contact with the battery cell to dissipate heat. The heat generated by the battery cell is carried away by the coolant. Its advantages include good temperature control, mature technology, good compatibility, and moderate cost.

[0003] When selecting materials for liquid cooling plates, the primary considerations are usually the material's pressure-bearing capacity and the product's corrosion resistance. Since the load-bearing pressure of energy storage batteries is concentrated on the liquid cooling plate, and it needs to maintain its shape under pressure for extended periods, the pressure-bearing capacity of the liquid cooling plate is critical. Liquid cooling plates are mainly classified into four types: friction stir welded (profile), flat tube cyclone, blow-blown, and stamped brazed. Profiles and brazed plates are currently the two mainstream types. Brazed plates have more variable flow channels and higher temperature uniformity, while friction stir welded plates have higher strength, fixed flow channels, and less uniform temperature distribution. Because brazed liquid cooling plates have relatively low strength, they need to be thickened or have steel components added to compensate for this weakness, limiting their application in the energy storage field.

[0004] Currently, brazed liquid cooling plates are mainly made of three-layer brazed aluminum-based composite materials. In traditional three-layer composite materials, the core material provides strength support, typically using an Al-Mn alloy. To improve strength, the Cu content in the core material is usually increased. While Cu has a certain solid solution strengthening effect, adding large amounts significantly reduces the material's corrosion resistance. Therefore, the upper limit of the strength of Al-Mn alloys is not high. Moreover, since Al-Mn alloys are not heat-treatable strengthening alloys, tensile strength may decrease after brazing. Considering the development trend of pressure-bearing requirements in new energy storage, the development of new high-strength, corrosion-resistant, and high-performance aluminum alloy composite materials represents a new development trend. Summary of the Invention

[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide a four-layer brazed aluminum composite material and a method for preparing the same, which has high strength and corrosion resistance.

[0006] Specifically, the first aspect of this application provides a four-layer brazed aluminum composite material, which, from bottom to top, comprises: Brazing layer: An aluminum alloy containing 9.3-9.8% Si, 0.02-0.04% Sr, and 0.05-0.1% Bi; Gradient barrier layer: An Al-Mn-Cu alloy with a compositional gradient distribution, wherein the Si content near the core is 0.8-1.0%, the Si content near the brazing side is 0.3-0.5%, and it contains 0.01-0.02% Ce; Core material: An Al-Mg-Si alloy containing 0.8-1.2% Mg, 0.4-0.8% Si, 0.08-0.12% Zr, and 0.04-0.06% Cr; Anti-corrosion layer: Al-Mn alloy containing 0.8-1.0% Mn and 0.05-0.1% Ti.

[0007] Furthermore, in the gradient barrier layer: The Ce element concentration decreases gradually from the core material side to the brazing side, with a decrease rate ≤5% / μm; and / or The thickness of the component transition zone accounts for ≥80% of the total thickness of the barrier layer.

[0008] Furthermore, the mass ratio of Zr to Cr in the core material is 1.5-3.0.

[0009] Furthermore, the thickness of the core material accounts for 63-68% of the total thickness of the composite material.

[0010] The second aspect of this application provides a method for preparing a four-layer brazed aluminum composite material, comprising the following steps: (a) Gradient barrier layer ingot preparation: A segmented casting process is adopted, first casting an alloy liquid containing 0.8-1.0% Si, then casting an alloy liquid containing 0.3-0.5% Si, with a casting interval of ≤30s; (b) Composite blank assembly: stacked in the order of brazing layer / gradient barrier layer / core material / anti-corrosion layer, and the interface is sandblasted or laser roughened; (c) Asynchronous temperature-controlled hot rolling: 3-5 passes of rolling are performed in the temperature range of 440-480℃, with an upper roll speed V h The lower roller speed V1 satisfies 1.12 ≤ V h / V1≤1.18; (d) Cold rolling and heat treatment: After cold rolling to the finished thickness, the product is annealed by pulse magnetic field and aged.

[0011] Furthermore, step (a) also includes using an electromagnetic stirring mixing transition zone with an electromagnetic stirring intensity of 100-150 rpm.

[0012] Furthermore, it also includes homogenization treatment of the core material, which involves treating it at 550-565℃ for 10-14 hours, cooling it to 460-480℃ for 7-9 hours, and then water quenching it.

[0013] Furthermore, in step (b): A gradient barrier layer is coated with a suspension containing CeO2 nanoparticles on the brazing side, with a coating thickness of 2-5 μm; and / or Assembly pressure ≥20MPa, fixed by four-corner argon arc welding.

[0014] Furthermore, in step (c), edge induction heating is applied simultaneously during the 3rd to 5th rolling passes, so that the edge temperature is 40-60°C higher than that of the center; and / or Final rolling temperature ≥350℃, and / or Total reduction rate ≥70%.

[0015] Furthermore, in step (d): The pulsed magnetic field annealing conditions are: temperature 340-360℃, magnetic field frequency 3-8Hz, magnetic field strength 0.3-0.8T; and / or The aging treatment conditions are: heat preservation at 170-190℃ for 6-10 hours.

[0016] The present invention has the following beneficial effects: (1) The brazing layer in the composite material of the present invention contains a specific proportion of Si, Sr and Bi elements. The synergistic effect of these elements endows the brazing layer with good brazing performance. Si element can lower the melting point of aluminum alloy and improve the fluidity of liquid brazing filler metal, so that it can better fill the weld gap during the brazing process and ensure the strength of the weld. Sr element has the effect of refining grains, which helps to improve the strength and toughness of the brazing layer and enhance its fatigue resistance. Bi element can improve the wettability of brazing filler metal, so that the brazing filler metal can better bond with the base material and improve the quality of the weld joint.

[0017] The gradient barrier layer employs an Al-Mn-Cu alloy with a compositional gradient distribution and contains a specific proportion of Ce. This compositional gradient allows the barrier layer to better adapt to the performance differences between the core material and the brazing layer, acting as a transition and buffer. The higher Si content near the core material enhances the bonding strength with the core material, while the lower Si content near the brazing side helps reduce the adverse effects on the brazing process. The Ce element concentration decreases gradient from the core material side to the brazing side, and the attenuation rate is strictly limited, which helps to further control element diffusion and improve the stability and performance consistency of the composite material. The required proportion of the compositional transition zone thickness to the total thickness of the barrier layer ensures that the gradient barrier layer can fully perform its barrier and transition functions.

[0018] The core material uses an Al-Mg-Si alloy containing specific proportions of Mg, Si, Zr, and Cr, with clear specifications for the Zr to Cr mass ratio and the core material thickness percentage. The presence of Mg and Si makes the core material a heat-treatable alloy, and aging treatment can significantly improve its strength. The addition of Zr and Cr refines the grain size, improving the core material's corrosion resistance and creep resistance. The appropriate Zr to Cr mass ratio and core material thickness percentage ensure that the core material can fully play its role in providing strength support and corrosion resistance within the composite material.

[0019] The anti-corrosion layer comprises an Al-Mn alloy with a specific ratio of Mn and Ti elements. Mn enhances the alloy's corrosion resistance, while Ti helps refine the grain size, strengthening the anti-corrosion layer and improving its stability. This anti-corrosion layer effectively protects the internal structure of the composite material from external corrosive media, extending its service life.

[0020] (2) Regarding the preparation method, the gradient barrier layer ingot preparation adopts a segmented casting process combined with electromagnetic stirring, which can precisely control the gradient distribution of alloy composition and ensure the performance of the gradient barrier layer. The treatment of the interface and the related coating and assembly requirements during the composite billet assembly process help to improve the bonding force between the layers and ensure the integrity of the composite material. The control of parameters such as temperature, roll speed ratio and edge heating during asynchronous temperature-controlled hot rolling can improve the microstructure of the composite material and enhance its mechanical properties. The setting of pulse magnetic field annealing and aging treatment conditions in the cold rolling and heat treatment steps further optimizes the performance of the composite material, enabling it to meet the requirements of high strength and corrosion resistance. The four-layer brazed aluminum composite material and its preparation method of the present invention, through reasonable material design and precise preparation process, successfully prepared a composite material with excellent properties such as high strength and corrosion resistance, meeting the strict requirements of liquid cooling plate materials in the energy storage field and having broad application prospects. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of this drawing or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this drawing. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0022] Figure 1 This is a schematic diagram of the structure of the four-layer brazed aluminum composite material of the present invention.

[0023] The purpose, features, and advantages of this accompanying drawing will be further explained in conjunction with the embodiments and with reference to the accompanying drawing. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this application clearer, the following description and illustration are provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application. All other embodiments obtained by those skilled in the art based on the embodiments provided in this application without inventive effort are within the scope of protection of this application.

[0025] Obviously, the following description is merely some examples or embodiments of this application. Those skilled in the art can apply this application to other similar scenarios without any inventive effort. Furthermore, it is understood that although the effort involved in such development may be complex and lengthy, for those skilled in the art related to the content disclosed in this application, any changes to design, manufacturing, or production based on the technical content disclosed in this application are merely conventional technical means and should not be construed as insufficient disclosure of the content of this application.

[0026] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0027] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0028] An embodiment of the first aspect of this application provides a four-layer brazed aluminum composite material, see [link to previous section]. Figure 1 From bottom to top, they include: Brazing layer: consists of 4045 aluminum alloy, Sr 0.02-0.04%, Bi 0.05-0.1%, with Si 9.3-9.8% and Fe ≤ 0.25%; the composition design of the brazing layer can lower the melting point and improve the fluidity of the brazing filler metal; the thickness ratio is 5±0.5%; Gradient barrier layer: Contains Fe 0.2-0.3%, Cu 0.7-0.8%, Mn 1.45-1.55%, Mg <0.03%, Zn <0.1%, Ti 0.10-0.13%, with the remainder being Al; this layer is an Al-Mn-Cu alloy with a compositional gradient distribution, wherein the Si content near the core is 0.8-1.0%, Ce 0.01-0.02%; the Si content near the brazing side is 0.3-0.5%; its high-Si region traps Mg, the low-Si region is compatible with brazing, and Ce cleans the interface; the thickness ratio is 17±1%; Core material: An Al-Mg-Si alloy consisting of 6061 aluminum alloy, Mg 0.8-1.2%, Si 0.4-0.8%, Zr 0.08-0.12%, and Cr 0.04-0.06%; Zr / Cr synergistic strengthening improves the strength and corrosion resistance of the core material; the thickness ratio is 65±2%.

[0029] Anti-corrosion layer: An Al-Mn alloy comprising Fe 0.2-0.3%, Cu 0.7-0.8%, Mn 0.8-1.0%, Mg <0.03%, Zn <0.1%, and Ti 0.05-0.1%. The thickness ratio is 13±1%; it is resistant to acidic coolant corrosion.

[0030] The composite material of this invention contains a brazing layer with specific proportions of Si, Sr, and Bi elements. The synergistic effect of these elements endows the brazing layer with excellent brazing performance. Si lowers the melting point of the aluminum alloy and improves the fluidity of the liquid brazing filler metal, allowing for better filling of the weld gap during brazing and ensuring weld strength. Sr refines the grain size, contributing to improved strength and toughness of the brazing layer and enhancing its fatigue resistance. Bi improves the wettability of the brazing filler metal, enabling better bonding between the filler metal and the base material, thus improving the quality of the weld joint.

[0031] The gradient barrier layer employs an Al-Mn-Cu alloy with a compositional gradient distribution. The Si content near the core is 0.8-1.0%, and the Si content near the brazing layer is 0.3-0.5%, with a Ce content of 0.01-0.02%. This compositional gradient distribution allows the barrier layer to better adapt to the performance differences between the core and the brazing layer, acting as a transition and buffer. The higher Si content near the core enhances the bonding strength with the core, while the lower Si content near the brazing layer helps reduce adverse effects on the brazing process. The Ce concentration decreases gradually from the core to the brazing layer with a strictly limited rate of decay, which helps to further control element diffusion and improve the stability and performance consistency of the composite material. The required proportion of the compositional transition zone thickness to the total thickness of the barrier layer ensures that the gradient barrier layer can fully perform its barrier and transition functions.

[0032] The core material uses an Al-Mg-Si alloy containing a specific ratio of Mg, Si, Zr, and Cr. The presence of Mg and Si makes the core material a heat-treatable alloy, and aging treatment can significantly improve its strength. The addition of Zr and Cr refines the grain size, improving the core material's corrosion resistance and creep resistance. A reasonable Zr to Cr mass ratio and core material thickness ensure that the core material can fully play its role in providing strength support and corrosion resistance within the composite material.

[0033] The anti-corrosion layer comprises an Al-Mn alloy with a specific ratio of Mn and Ti elements. Mn enhances the alloy's corrosion resistance, while Ti helps refine the grain size, strengthening the anti-corrosion layer and improving its stability. This anti-corrosion layer effectively protects the internal structure of the composite material from external corrosive media, extending its service life.

[0034] In this embodiment, in the gradient barrier layer: the Ce element concentration decreases gradually from the near-core side to the near-brazing side, with an attenuation rate ≤5% / μm; the thickness of the composition transition region accounts for ≥80% of the total thickness of the barrier layer. This gradient attenuation characteristic of Ce element in the gradient barrier layer further optimizes the performance of the barrier layer. By precisely controlling the rate and range of element diffusion, it enables the gradient barrier layer to exhibit physical and chemical properties that are more compatible with adjacent layers in different regions. On the side closer to the core material, the higher Ce element concentration helps to enhance the bonding force with the core material and, to a certain extent, promotes elemental interaction between the core material and the gradient barrier layer, forming a more stable interface structure. As the transition proceeds towards the near-brazing side, the gradient attenuation of Ce element concentration effectively avoids adverse effects on the brazing process, ensuring good brazing performance of the brazing layer.

[0035] Meanwhile, the thickness of the compositional transition zone must account for no less than 80% of the total thickness of the barrier layer. This design ensures that the gradient barrier layer can fully perform its transition and buffering functions. A thicker compositional transition zone makes the performance changes within the gradient barrier layer smoother, better accommodating the significant performance differences between the core material and the brazing layer. In practical applications, this smooth performance transition can reduce stress concentration within the composite material under stress or heat, improving the overall stability and reliability of the composite material.

[0036] Furthermore, this gradient barrier layer design also positively impacts the corrosion resistance of the composite material. Ce has certain antioxidant and corrosion-resistant capabilities, and its gradient distribution within the barrier layer can form an effective corrosion barrier throughout the entire layer. The variation in Ce concentration from the near-core side to the near-brazing side allows for targeted protection based on the corrosion risk in different areas, further enhancing the composite material's ability to resist external corrosive media.

[0037] In this embodiment, the mass ratio of Zr to Cr in the core material is 1.5-3.0. This ratio allows the two elements to exert their optimal synergistic effect in refining grain size, improving corrosion resistance, and creep resistance. When the Zr to Cr mass ratio is within this range, Zr can fully utilize its ability to refine grain size, resulting in a more uniform and dense microstructure of the core material. Simultaneously, Cr, when in a suitable ratio, can also work synergistically with Zr to further enhance the corrosion resistance of the core material.

[0038] Regarding creep resistance, a proper ratio of Zr and Cr can effectively hinder dislocation movement and improve the stability of the core material under high temperature and long-term stress. When the Zr to Cr mass ratio is less than 1.5, the relatively high Cr content may lead to insignificant grain refinement and difficulty in achieving an optimal balance in corrosion resistance. Conversely, when the Zr to Cr mass ratio is greater than 3.0, the excessive Zr content may negatively impact the core material's strength and other performance indicators to some extent.

[0039] Furthermore, the optimal Zr to Cr mass ratio is closely related to the aging treatment effect of the core material. During the aging process, the synergistic effect of Zr and Cr promotes the uniform precipitation of the precipitate phase, thereby significantly improving the strength of the core material. This optimized core material can better fulfill its role in strength support and corrosion resistance in the composite material, ensuring that the entire four-layer brazed aluminum composite material maintains good performance under complex working environments and meets the stringent requirements for liquid cooling plate materials in the energy storage field.

[0040] In this embodiment, the core material accounts for 63-68% of the total thickness of the composite material. This thickness ratio design fully considers the core material's central position and crucial role in the composite material. As the main load-bearing structure of the composite material, the core material's thickness ratio of 63-68% provides sufficient strength support for the entire composite material. When used in liquid-cooled plates in energy storage applications, these plates need to withstand certain pressure and temperature changes. A higher core material thickness ratio ensures that the liquid-cooled plate will not deform or be damaged under these complex operating conditions, guaranteeing the stability and reliability of its structure.

[0041] From a materials performance perspective, the elements such as Mg, Si, Zr, and Cr contained in the core material endow it with excellent strength and corrosion resistance. The relatively large thickness allows these superior properties of the core material to be fully realized in the composite material. On the one hand, when facing corrosive media, a sufficiently thick core material provides stronger corrosion resistance for the entire composite material; on the other hand, when subjected to external forces, the core material can effectively disperse stress, preventing stress concentration that could lead to material failure.

[0042] Furthermore, a reasonable core material thickness ratio also facilitates synergy with other layers. The gradient barrier layer and the anti-corrosion layer can better integrate with the core material, working together to fulfill their respective functions. The gradient barrier layer can better adapt to the performance differences between the core material and the brazed layer, acting as a transition and buffer; the anti-corrosion layer can more effectively protect the core material from external corrosion. This synergistic effect between the layers allows the entire four-layer brazed aluminum composite material to achieve optimal performance balance, meeting the stringent requirements of the energy storage field for liquid cooling plate materials in terms of high strength, corrosion resistance, and other aspects, further expanding the scope and prospects of this composite material in practical applications.

[0043] An embodiment of the second aspect of this application provides a method for preparing a four-layer brazed aluminum composite material, comprising the following steps: (a) Gradient barrier layer ingot preparation: A segmented casting process is adopted. First, an alloy liquid containing 0.8-1.0% Si and 0.01-0.02% Ce is poured into the bottom (near the core material), followed by an alloy liquid containing 0.3-0.5% Si, with a pouring interval ≤30s. An electromagnetic stirring casting furnace is used, with an electromagnetic stirring speed of 100-150 rpm. The composition in the transition zone changes linearly (R0). 2 ≥0.95), transition zone thickness ≥80%; The core material is homogenized by treating it at 550-565℃ for 10-14 hours, cooling it to 460-480℃ for 7-9 hours, and then water quenching it. (b) Composite preform assembly: The preforms are stacked in the following order: brazing layer / gradient barrier layer / core material / anti-corrosion layer. The interfaces are sandblasted or laser-textured. The brazing layer is sandblasted, and the gradient barrier layer is coated with a suspension containing CeO2 nanoparticles near the brazing side, with a coating thickness of 2-5 μm. The core material is preheated to 200°C, and the composite surface of the anti-corrosion layer is laser-textured with a dot density of 200 dots / cm. 2 The depth is 50μm; the four corners are fixed by argon arc welding, the current is 180A, the weld length is 400mm, and the steel strip pressure is 20-28MPa; (c) Perform hot rolling composite process, including the first rolling pass, with an initial rolling temperature of 480±10℃, a final rolling temperature of 450±10℃, a reduction of 16mm, and a roll speed ratio V. h V1 = 1.0:1, and the emulsion is turned off; The second rolling pass has an initial rolling temperature of 460±10℃ and a final rolling temperature of 430±10℃. The reduction is 30mm, and the roll speed ratio V is... h V1 = 1.05:1, emulsion flow rate is 200 L / min.

[0044] For rolling passes 3-5, the initial rolling temperature is 440±5℃, the final rolling temperature is ≥350℃, the reduction is 30mm / pass, and the upper roll speed is V. hThe lower roller speed V1 satisfies 1.12 ≤ V h / V1≤1.18, asynchronous rolling generates shear stress, promoting interfacial diffusion bonding; simultaneous edge induction heating is applied with a power of 50kW, raising the edge temperature by 40-60℃ higher than the center to suppress edge cracking; emulsion flow rate is 200L / min; total reduction ≥70%; final rolling: initial rolling temperature 380±10℃, final rolling temperature ≥300℃, reduction 25mm / pass, roll speed ratio V h V1 = 1.05:1, emulsion flow rate is 400 L / min.

[0045] (d) Cold rolling and heat treatment: After cold rolling to the finished thickness, the product is annealed by pulse magnetic field and aged.

[0046] Among them, the roughing rolling is 7.0mm→5.5mm (reduction rate 21%); the intermediate rolling is 5.5mm→4.2mm (reduction rate 24%); and the finishing rolling is 4.2mm→3.0±0.03mm (reduction rate 28.6%, rolling force ≤800T). The pulsed magnetic field annealing conditions are: temperature 340-360℃ for 1.5-2.5h, magnetic field frequency 3-8Hz, and magnetic field strength 0.3-0.8T; the aging treatment conditions are: 170-190℃ for 6-10h.

[0047] In the above preparation method, the segmented casting process of the gradient barrier layer ingot, through precise control of the casting interval and electromagnetic stirring parameters, ensures the uniformity of the composition and the accuracy of the gradient distribution within the ingot. The casting interval of less than 30 seconds allows alloy liquids with different Si contents to fuse at the appropriate time, avoiding excessive mixing or separation of components and ensuring that the Si content near the core material and near the brazing side meets design requirements. The electromagnetic stirring furnace, with a stirring speed of 100-150 rpm, not only facilitates the uniform mixing of the alloy liquid but also ensures a linear gradient in the composition of the transition zone, with a transition zone thickness ≥80%. This lays a solid foundation for the subsequent gradient barrier layer to exert its transition and buffering effects.

[0048] Homogenization treatment of the core material is a key step in improving its performance. Treatment at 550-565℃ for 10-14 hours allows for sufficient diffusion of elements within the core, eliminates component segregation, and improves the uniformity of the core's microstructure. Subsequent cooling to 460-480℃ for 7-9 hours further adjusts the core's microstructure, achieving a more stable state. Finally, water quenching rapidly cools the core, preserving the beneficial microstructure and properties formed during the high-temperature treatment, providing a high-quality core material foundation for subsequent composite processing.

[0049] During the assembly of the composite preform, the processing methods and welding parameters of each layer were carefully designed. Sandblasting or laser texturing of the interfaces increased the surface roughness between layers, improving interlayer bonding. Sandblasting of the brazing layer removed surface impurities and improved brazing performance; the gradient barrier layer was coated with a suspension containing CeO2 nanoparticles near the brazing side, with a coating thickness of 2-5 μm. The CeO2 nanoparticles improved the physical and chemical properties of the interface, enhancing the interlayer bonding strength and stability; preheating the core material to 200℃ facilitated better bonding with other layers during the composite process; and laser texturing of the anti-corrosion layer composite surface resulted in a dot density of 200 dots / cm². 2 The depth of 50μm not only increases the surface roughness but also improves the surface properties of the anti-corrosion layer to a certain extent. The four-corner argon arc welding method, with a current of 180A, a weld length of 400mm, and a steel strip pressure of 20-28MPa, ensures a tight bond between the layers of the composite billet and prevents interlayer separation during subsequent processing.

[0050] Multi-pass rolling and edge induction heating in hot rolling composite processes are crucial for achieving effective bonding between layers and controlling the properties of composite materials. Different rolling passes, through precise control of parameters such as initial rolling temperature, final rolling temperature, reduction, and roll speed ratio, gradually alter the thickness and microstructure of the composite material, promoting interfacial diffusion bonding between layers. The shear stress generated by asynchronous rolling further enhances the interlayer bonding force, allowing for more complete atomic diffusion between layers. Edge induction heating technology ensures that the edge temperature is 40-60°C higher than the center, effectively suppressing edge cracking and guaranteeing the quality and dimensional accuracy of the composite material. A total reduction rate of ≥70% ensures the tightness of the bonding between layers and the overall performance of the composite material.

[0051] The cold rolling and heat treatment processes further optimize the performance of the composite material. Controlling the reduction rate at different stages of cold rolling allows the composite material to achieve the required finished thickness and surface quality. Pulsed magnetic field annealing, performed at 340-360℃ for 1.5-2.5 hours with a magnetic field frequency of 3-8 Hz and a magnetic field strength of 0.3-0.8 T, eliminates internal stress generated during cold rolling, improves the microstructure of the composite material, and enhances its strength and toughness. Aging treatment at 170-190℃ for 6-10 hours further precipitates and strengthens the elements in the composite material, significantly improving its overall performance and enabling it to better meet the stringent requirements for liquid-cooled plate materials in the energy storage field.

[0052] In summary, the four-layer brazed aluminum composite material and its preparation method provided in this application achieve synergistic effects between the layers through the rational design of each layer and the precise control of the preparation process. This results in a composite material with excellent brazing performance, strength, corrosion resistance, and stability, providing a high-performance material solution for liquid cooling plate applications in the energy storage field. Example The following examples describe the disclosure of this invention in more detail. These examples are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of this disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight. Unless otherwise stated, all reagents used in the examples are available commercially or synthesized using conventional methods and are ready for use without further processing. Unless otherwise stated, all instruments used in the examples are available commercially.

[0053] Example 1 A four-layer brazed aluminum composite material, comprising, from bottom to top: Brazing layer: 4045 aluminum alloy, Sr 0.03%, Bi 0.08%, of which Si 9.5% and Fe≤0.25%; Gradient barrier layer: Fe 0.25%, Cu 0.75%, Mn 1.5%, Mg 0.02%, Zn 0.09%, Ti 0.12%, with the remainder being Al; of which the side near the core material contains Si 1.0% and Ce 0.02%; and the side near the brazing layer contains Si 0.4%. Core material: Al-Mg-Si alloy of 6061 aluminum alloy, Mg 1%, Si 0.6%, Zr 0.10%, and Cr 0.05%; Anti-corrosion layer: Al-Mn alloy with Fe 0.25%, Cu 0.78%, Mn 0.9%, Mg 0.025%, Zn 0.08%, and Ti 0.08%.

[0054] The preparation method of the aforementioned four-layer brazed aluminum composite material includes the following steps: (a) Gradient barrier layer ingot preparation: A segmented casting process was adopted. The bottom (near the core material) was first poured with an alloy liquid containing 1.0% Si and 0.02% Ce, followed by an alloy liquid containing 0.4% Si, with a pouring interval of ≤30s; an electromagnetic stirring casting furnace was used, with an electromagnetic stirring speed of 120rp and a transition zone thickness of 85%; The core material is homogenized by treating it at 560℃ for 12 hours, cooling it to 470℃ for 8 hours, and then water quenching it. (b) Composite preform assembly: The preforms are stacked in the following order: brazing layer / gradient barrier layer / core material / anti-corrosion layer. The interfaces are sandblasted or laser-textured. The brazing layer is sandblasted, and the gradient barrier layer is coated with a suspension containing CeO2 nanoparticles near the brazing side, with a coating thickness of 2-3 μm. The core material is preheated to 200℃, and the composite surface of the anti-corrosion layer is laser-textured with a dot density of 200 dots / cm. 2 The depth is 50μm; the four corners are fixed by argon arc welding, the current is 180A, the weld length is 400mm, and the steel strip pressure is 25MPa; (c) Perform hot rolling composite process, including the first rolling pass, with an initial rolling temperature of 480°C, a final rolling temperature of 450°C, a reduction of 16 mm, and a roll speed ratio V. h V1 = 1.0:1, and the emulsion is turned off; The second rolling pass has an initial rolling temperature of 460℃, a final rolling temperature of 430℃, a reduction of 30mm, and a roll speed ratio V. h V1 = 1.05:1, emulsion flow rate is 200 L / min.

[0055] For rolling passes 3-5, the initial rolling temperature is 440℃, the final rolling temperature is 360℃, the reduction is 30mm / pass, and the upper roll speed is V. h The lower roller speed V1 satisfies V h / V1=1.15:1, asynchronous rolling generates shear stress, promoting interfacial diffusion bonding; simultaneous edge induction heating is applied with a power of 50kW, raising the edge temperature by 50°C compared to the center to suppress edge cracking; emulsion flow rate is 200L / min; total reduction is 70%; final rolling: initial rolling temperature is 380°C, final rolling temperature is 300°C, reduction is 25mm / pass, and roll speed ratio V h V1 = 1.05:1, emulsion flow rate is 400 L / min; (d) Cold rolling and heat treatment: After cold rolling to the finished thickness, the product is annealed by pulse magnetic field and aged. Among them, the roughing rolling is 7.0mm→5.5mm (reduction rate 21%); the intermediate rolling is 5.5mm→4.2mm (reduction rate 24%); and the finishing rolling is 4.2mm→3.0±0.03mm (reduction rate 28.6%, rolling force ≤800T). The pulsed magnetic field annealing conditions are: temperature 350℃ for 2 hours, magnetic field frequency 5Hz, and magnetic field strength 0.5T; the aging treatment conditions are: 180℃ for 8 hours.

[0056] Example 2 This embodiment is basically the same as Embodiment 1, except that: the brazing layer contains 0.04% Sr and 0.05% Bi; the gradient barrier layer contains 0.9% Si and 0.01% Ce near the core material and 0.5% Si near the brazing material.

[0057] Example 3 This embodiment is basically the same as Embodiment 1, except that: the core material contains 0.12% Zr and 0.04% Cr; and the anti-corrosion layer contains 1.0% Mn and 0.05% Ti.

[0058] Example 4 This embodiment is basically the same as Embodiment 1, except that: Sr 0.02% and Bi 0.1% are in the brazing layer; Si 0.8% and Ce 0.02% are in the gradient barrier layer near the core material, and Si 0.3% is in the brazing layer.

[0059] Example 5 This embodiment is basically the same as Embodiment 1, except that the core material contains 0.15% Zr and 0.03% Cr.

[0060] Comparative Example 1 This comparative example is basically the same as Example 1, except that the brazing layer uses only 4045 aluminum alloy and the core material uses only 6061 aluminum alloy.

[0061] Comparative Example 2 This comparative example is basically the same as Example 1, except that the barrier layer does not use a gradient treatment, and Si is 0.6%.

[0062] Comparative Example 3 This comparative example is basically the same as Example 1, except that the core material does not contain Zr or Cr.

[0063] Comparative Example 4 This comparative example is basically the same as Example 1, except that no edge compensation is performed during the 3rd to 5th rolling passes.

[0064] Comparative Example 5 This comparative example is basically the same as Example 1, except that V during the 3rd to 5th rolling passes h / V1=1.0:1.

[0065] Experimental Case The performance of the composite boards prepared in Examples 1-5 and Comparative Examples 1-5 was tested, and the results are shown in Table 1.

[0066]

[0067] As shown in Table 1, the composite plates prepared in Examples 1-5 are superior to those in Comparative Examples 1-5 in terms of tensile strength, salt spray life, and hot rolling yield. Regarding tensile strength, the values ​​in the examples are significantly higher than those in the comparative examples, indicating that the precise control of the material composition and preparation process of each layer in this application can significantly improve the strength of the composite material. For example, the tensile strength of Example 4 reaches 242 MPa, while that of Comparative Example 1 is only 185 MPa. In terms of salt spray life, the composite plates in the examples exhibit good corrosion resistance. The salt spray life of Example 1 is 1320 h, far exceeding the 700 h of Comparative Example 1, indicating that the synergistic effect of each layer and the rational design of the gradient barrier layer and anti-corrosion layer effectively enhance the corrosion resistance of the composite material. As for the hot rolling yield, the examples generally have higher yields, which is attributed to the precise process control, such as multi-pass rolling and edge induction heating technology, in the hot rolling composite process. For example, the hot rolling yield of Example 1 is 98.5%, while that of Comparative Example 1 is only 84.3%, indicating that the preparation method of this application can effectively ensure the quality and stability of the composite material during the hot rolling process.

[0068] Comparative Example 1 uses only conventional aluminum alloy as the brazing layer and core material without composition optimization, resulting in significantly lower performance indicators compared to the Example. This may be because conventional aluminum alloys have a single composition and lack the synergistic effect of other elements, failing to form an effective strengthening mechanism and corrosion-resistant structure. During brazing, ordinary aluminum alloys cannot achieve good bonding and interfacial reactions with other layers like the brazing layer with optimized composition in this application, affecting the overall strength and stability of the composite material. Furthermore, aluminum alloys without special element additions have limited corrosion resistance and are unable to withstand the erosion of harsh environments such as salt spray, resulting in a shorter salt spray life.

[0069] In Comparative Example 2, the barrier layer lacks a gradient treatment, preventing it from fulfilling its intended transition and buffering functions. In composite materials, the gradient design of a gradient barrier layer enables a smooth transition in composition and properties between different layers, avoiding stress concentration and poor interfacial bonding caused by excessive differences in composition and properties. When the barrier layer lacks a gradient treatment, the performance differences between the near-core and near-brazing sides cannot be effectively adjusted, weakening the synergistic effect between layers and consequently affecting the overall performance of the composite material, such as a decrease in tensile strength and salt spray life.

[0070] Comparative Example 3's core material does not contain elements such as Zr and Cr. Zr and Cr, in the core material, can refine grains, improve microstructure stability, and enhance corrosion resistance. Without these elements, the core material's internal structure is less stable, and grains are prone to growth, thus reducing its strength and toughness. Simultaneously, in terms of corrosion resistance, Zr and Cr can form a stable oxide film on the core material surface, improving its corrosion resistance. When these elements are lacking in the core material, the composite material's corrosion resistance and strength are affected, resulting in performance indicators that are inferior to those of the examples.

[0071] In Comparative Example 4, edge compensation was not performed during the 3rd to 5th rolling passes. Edge induction heating technology is an important method in the hot rolling composite process of this application. It can make the edge temperature 40-60℃ higher than the center, effectively suppressing edge cracking. Without edge compensation, the edge temperature is lower during rolling, the material's plastic deformation capacity is reduced, and defects such as edge cracking are more likely to occur, reducing the hot rolling yield. Moreover, edge cracking defects also affect the overall quality and dimensional accuracy of the composite material, further affecting its tensile strength and other properties.

[0072] In Comparative Example 5, during the 3rd to 5th rolling passes, Vh / V1 = 1.0:1, meaning asynchronous rolling was not used to generate shear stress. The shear stress generated by asynchronous rolling can further enhance the interlayer bonding force, allowing for more complete atomic diffusion between layers. When asynchronous rolling is not used, the interlayer bonding force is relatively weak, and atomic diffusion is insufficient, resulting in less tight interfacial bonding between layers, thus affecting the tensile strength and other properties of the composite material. In summary, this application, through the rational design of each layer material and precise control of the preparation process, achieves synergistic effects between layers, significantly improving the performance of the composite material and providing a high-performance material solution for liquid-cooled plate applications in the energy storage field.

[0073] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A four-layer brazed aluminum composite material, characterized in that, From bottom to top, they include: Brazing layer: An aluminum alloy containing 9.3-9.8% Si, 0.02-0.04% Sr, and 0.05-0.1% Bi; Gradient barrier layer: An Al-Mn-Cu alloy with a compositional gradient distribution, wherein the Si content near the core is 0.8-1.0%, the Si content near the brazing side is 0.3-0.5%, and it contains 0.01-0.02% Ce; the Ce element concentration decreases gradually from the near-core side to the near-brazing side, with an attenuation rate ≤5% / μm; the thickness of the compositional transition region accounts for ≥80% of the total thickness of the barrier layer; Core material: An Al-Mg-Si alloy containing 0.8-1.2% Mg, 0.4-0.8% Si, 0.08-0.12% Zr, and 0.04-0.06% Cr; Anti-corrosion layer: Al-Mn alloy containing 0.8-1.0% Mn and 0.05-0.1% Ti.

2. The four-layer brazed aluminum composite material according to claim 1, characterized in that, The mass ratio of Zr to Cr in the core material is 1.5-3.

0.

3. The four-layer brazed aluminum composite material according to claim 1, characterized in that, The thickness of the core material accounts for 63-68% of the total thickness of the composite material.

4. A method for preparing a four-layer brazed aluminum composite material according to any one of claims 1-3, characterized in that, Includes the following steps: (a) Gradient barrier layer ingot preparation: A segmented casting process is adopted, first casting an alloy liquid containing 0.8-1.0% Si, then casting an alloy liquid containing 0.3-0.5% Si, with a casting interval of ≤30s; (b) Composite blank assembly: stacked in the order of brazing layer / gradient barrier layer / core material / anti-corrosion layer, and the interface is sandblasted or laser roughened; (c) Asynchronous temperature-controlled hot rolling: 3-5 passes of rolling are performed in the temperature range of 440-480℃, with an upper roll speed V h The lower roller speed V1 satisfies 1.12 ≤ V h / V1≤1.18; (d) Cold rolling and heat treatment: After cold rolling to the finished thickness, the product is annealed by pulse magnetic field and aged.

5. The method for preparing the four-layer brazed aluminum composite material according to claim 4, characterized in that, Step (a) also includes using an electromagnetic stirring mixing transition zone with an electromagnetic stirring intensity of 100-150 rpm.

6. The method for preparing the four-layer brazed aluminum composite material according to claim 4, characterized in that, It also includes homogenizing the core material, with the process being to treat it at 550-565℃ for 10-14 hours, cool it to 460-480℃ for 7-9 hours, and then water quench it.

7. The method for preparing the four-layer brazed aluminum composite material according to claim 4, characterized in that, In step (b): A gradient barrier layer is coated with a suspension containing CeO2 nanoparticles on the brazing side, with a coating thickness of 2-5 μm; and / or Assembly pressure ≥20MPa, fixed by four-corner argon arc welding.

8. The method for preparing the four-layer brazed aluminum composite material according to claim 4, characterized in that, In step (c), during the 3rd to 5th rolling passes, edge induction heating is applied simultaneously to make the edge temperature 40-60°C higher than the center temperature; and / or Final rolling temperature ≥350℃, and / or Total reduction rate ≥70%.

9. The method for preparing the four-layer brazed aluminum composite material according to claim 4, characterized in that, In step (d): The pulsed magnetic field annealing conditions are: temperature 340-360℃, magnetic field frequency 3-8Hz, magnetic field strength 0.3-0.8T; and / or, the aging treatment conditions are: 170-190℃ for 6-10h.

Citation Information

Patent Citations

  • Soldering flux-free soldering aluminum alloy material and preparation method thereof

    CN104626674A

  • Brazing method for aluminum alloy brazing sheet and method for producing heat exchanger

    CN110662626A